The participation of women in the Family Farming and Popular Economy Solidarity Fair in the Inhamuns and Crateús territory of Ceará - Ydávila Vasconcelos Martins; Lia Pinheiro Barbosa (Universidade Federal do Norte do Tocantins, 2022)
The article aims to analyze the participation of women in the Family Farming and Popular Economy Solidarity Fair in the territory of Inhamuns and Crateús, in Ceará, organized by Caritas of the Diocese of Crateús. To this end, we contextualized the emergence of the fair in the region, based on the systematization of this experience in the context of the articulation of different subjects. The research was based on a qualitative approach through bibliographic research and field research, with the following categories: Solidarity Economy; Popular Solidarity Economy and Feminist Economy. We sustain two arguments resulting from the research: (a) the Family Farming and Popular Solidarity Economy Fair of the territory of Inhamuns and Crateús builds a subjectivity linked to Rural Education and the so-called Pedagogy of the Movement, especially by strengthening the identity with the peasant territory linked to family and peasant production ,and, (b) women contribute to this process in an educational-pedagogical dimension, since they are formed within the Fair, while influencing the nature of the Fair, especially by their contribution to the strengthening of the Popular Solidarity Economy in a feminist perspective.